Later adults' cultural life scripts of middle and later adulthood. Issue 3 (4th May 2018) - Grysman, Azriel; Dimakis, Sarah
ABSTRACT: The cultural life script (CLS) refers to expected prototypical life events, often including life transitions overwhelmingly occurring at ages 11-30. This study outlined CLS events at ages after the majority of these events typically occur. Participants, age 38-76, nominated events they expected a person of their age to experience in the future. Participants rated each event's valence, importance, prevalence, and expected age of occurrence. Events were coded into three categories: the normative CLS for events listed by previous CLS studies,  offspring's CLS for experiencing CLS events of offspring, and later adulthood CLS for other events nominated by at least 4% of participants. Results suggest scripted events highlighting positivity and change. Offspring's CLS was more positive and occurred earlier than others. Correlations emerged between event characteristics and well-being. Results affirm the prominence of transitions in memory, and suggest ways that older adults maintain well-being despite a cultural narrative that emphasizes decline.